STRATEGI BRANDING DIGITAL UNTUK DESA WISATA DI BANYUWANGI BERBASIS PENDEKATAN PARTISIPATIF DAN INOVASI LOKAL - Fajar Isnaeni; Nikma Yucha (LPPM Universitas Bhayangkara Surabaya, 2025)
TStrengthening the digital capacity of tourism villages is a strategic need in increasing the competitiveness of local tourism in the digital era. This article aims to formulate a participatory digital branding strategy and local innovation in Banyuwangi tourism villages. Using a descriptive qualitative approach with a participatory method, data was collected through interviews, FGDs, and direct observation of tourism village actors, Pokdarwis, and local MSME actors. The results show that digital training and mentoring have succeeded in improving the community's ability to create promotional content, compile cultural narratives, and manage village social media independently. This strategy contributes to the theory of community empowerment and locally-based tourism, as well as opens up space for model replication for other tourist villages. The conclusion of this activity emphasizes the importance of synergy between technology, culture, and community participation in building strong village tourism destination branding.